Series of Carbazole–Pyrimidine Conjugates: Syntheses and Electronic, Photophysical, and Electrochemical Properties - Kato, Shin-ichiro; Yamada, Yuji; Hiyoshi, Hidetaka; Umezu, Kazuto; Nakamura, Yosuke (Journal of organic chemistry, 2015)
A series of carbazole–pyrimidine conjugates 1–17 were synthesized by Pd-catalyzed cross-coupling, oxidation, and nucleophilic aromatic substitution reactions. In 1–17, the carbazole moieties are connected at the 4,6-positions of the pyrimidine ring either directly or via ethynylene or vinylene spacers, and various electron-donating or electron-withdrawing substituents are introduced at the 2-position of the pyrimidine ring. The effects of structural variations on the electronic, photophysical, and electrochemical properties of 1–17 were comprehensively investigated. Compounds 1–17 exhibit intramolecular charge-transfer (ICT) states, which essentially lead to moderate-to-strong fluorescence emission with large Stokes shifts depending on the solvent polarity. These compounds tend to show significant changes in optical and fluorescence properties upon addition of trifluoroacetic acid. The electron-accepting ability of these compounds can be tuned by both substituents on the pyrimidine moiety and spacers. The ethynylene spacer lowers both the HOMO and LUMO levels, while the vinylene spacer elevates the HOMO level and lowers the LUMO level. The X-ray crystal structures of 3, 6, 11, and 14 are also disclosed.